2015
DOI: 10.1002/nau.22903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a distraction task on the involuntary reflex contraction of the pelvic floor muscles following cough

Abstract: The mental distraction task altered involuntary reflex contraction of the pelvic floor muscles. Neurourol. Urodynam. 36:160-165, 2017. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 27 publications
5
35
0
2
Order By: Relevance
“…They also showed that an altered modulation of pelvic contraction during cough efforts is found in women presenting SUI . Furthermore, this SUI seemed to be modulated by attention …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They also showed that an altered modulation of pelvic contraction during cough efforts is found in women presenting SUI . Furthermore, this SUI seemed to be modulated by attention …”
Section: Discussionmentioning
confidence: 89%
“…We used the previous methodology for EMG recordings . EMG recordings were made with a pair of pregelled surface self‐adhesive electrode (Figure ; REF: EL 503; BIOPAC Systems Inc., Goleta, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Considering an expected difference of 30% between the two groups regarding the latency between the onset of the involuntary EAS EMG activation and the onset of the EIC EMG activation (RT3) after rehabilitation (meaning that we expected a 30% faster perineal pre‐contraction in response to cough effort in women who underwent double task rehabilitation, compared with the control group), and a power of 95% and an α ‐risk of 0.05, 13 volunteers were included in each group. Thirty percent was chosen because in the case of a DT, we previously showed that latency of the perineal pre‐contraction was 30% shorter . To improve the power of our study, two controls were included for each patient included in the rehabilitation group.…”
Section: Methodsmentioning
confidence: 99%
“…In continent women, we previously observed that a mental DT altered reaction time (RT) between an order to contract PFM and the onset of PFM contraction activation . In the same way, during a mental DT, the RT between the initiation of cough effort (activation of the external intercostal muscles) and the onset of the PFM contraction is delayed . In the same way, during a mental DT, the RT between the initiation of cough effort (activation of the EIC muscles) and the onset of the PFM contraction is delayed .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation